Quo Vadis: Establishment of a Land Bank after the Decision of the Constitutional Court of the Republic of Indonesia Number 91/PUU-XVIII/2020 - Ardhanariswari, Riris; Nursetiawan, Eko (KnE Social Sciences, 2023)
This study aims to examine and analyze the formation of a land bank after the Decision of the Constitutional Court of the Republic of Indonesia, Number 91/PUU-XVIII/2020, which was declared conditionally unconstitutional. The research method used is normative juridical research, which involves examining and inventorying various secondary data, namely library research. Based on the results of the research and discussion, it can be concluded that, first, the existence of a land bank, which is included in the cluster of Law Number 11 of 2020 concerning Job Creation, makes it relatively difficult to carry out its duties and authorities because, as the Constitutional Court stated in Decision Number 91/PUU-XVIII/2020, it was declared conditionally unconstitutional, so the government was prohibited from enacting implementing regulations or derivative regulations from a quo. Second, the government should comply with the decision of the Constitutional Court of the Republic of Indonesia as a check and balance; therefore, the DPR and the President must first improve the Job Creation Law so that land banks can carry out their functions and authorities. Keywords: constitutional court, land, land bank